The "Archeology of Knowledge" in Ricardo Palma - Arista Montoya, Luis (2019)
The “Carta Tónico-biliosa” written in 1874 by the young Ricardo Palma has a philosophical significance. Thus, in there he points out a kind of declaration of ethical and aesthetic principles, which will not only set his personal creative path but that of his entire generation. In this letter, he proposes to develop an “archaeology of knowledge” to understand better the republican birth of the Peruvian nation.